Challenges and innovations: adapting practical culinary and foodservice subjects for distance learning during COVID-19 / Mohd Shazali Md Sharif, Faradewi Bee A. Rahman and Mohd Noor Azmin Akbarruddin - Md Sharif, Mohd Shazali; A Rahman, Faradewi Bee; Akbarruddin, Mohd Noor Azmin (Universiti Teknologi MARA, Kedah, 2024)
This article presents an overview of the challenges and innovative solutions encountered in adapting practical culinary and foodservice subjects for distance learning during the COVID-19 pandemic. The study explores the limitations of remote learning in culinary education, including the loss of hands-on experience, limited access to specialized resources, the assessment of practical skills, and the impact on students' emotional well-being. To address these challenges, educators have implemented various innovative approaches. Virtual cooking demonstrations, interactive online modules, and simulations have been utilized to recreate practical experiences and engage students in a virtual environment. Collaborations with industry professionals and the establishment of online communities have facilitated networking, industry insights, and peer learning. Furthermore, future directions are discussed, including the integration of advanced technologies such as virtual reality and augmented reality for a more immersive practical learning experience. Collaborative online platforms and the utilization of technology-enhanced assessments are suggested to enhance student engagement and provide authentic learning experiences. Lastly, continuous professional development for educators is emphasized to ensure effective distance learning practices. The findings presented in this abstract contribute to the ongoing discourse surrounding distance learning in culinary education. By highlighting the limitations, innovative solutions, and future directions, this article aims to inspire further research and advancements in the field. The resilience, adaptability, and commitment exhibited by educators and students in delivering high-quality culinary education remotely during these challenging times underscore the importance of embracing technology and continuous improvement to enrich culinary education practices in the digital era.